DIGITALISASI PROMOSI DAN EDUKASI TRANSAKSI NIRTUNAI (QRIS) PADA UMKM DESA PEDATARAN MELALUI KONTEN VIDEO PENDEK TIKTOK - Oktaviana, Nova; Armasito Armasito (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
The development of digital technology offers great opportunities for Micro, Small, and Medium Enterprises (MSMEs) in rural areas to expand their market reach. However, limited digital literacy often causes business actors to not optimize social media as a marketing instrument. This community service activity aims to help digitalize promotion while educating the public regarding cashless payment methods (QRIS) at the "Warung Teras Ibu" MSME in Pedataran Village, Gelumbang District. The implementation method uses a Digital Community Service approach through the creation of short video content uploaded to the TikTok platform (@kkn84_kel38uinrf). The stages of the activity include observation, taking food review videos, demonstrating QRIS payments, and visual editing. The results of the community service show that the utilization of the TikTok algorithm is very effective in boosting the visibility of local MSMEs. In a short time, the promotional content successfully reached 2,775 views, 67 likes, and 2 shares. In addition, the integration of the QRIS demonstration in the video proved to be a catalyst for inclusive digital financial literacy education for the wider community. This activity concludes that digital marketing interventions carried out by KKN students are able to break the geographical isolation of rural MSMEs, introduce local products to a wider audience, and support the acceleration of cashless financial inclusion in the region.